(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Tourism is one of the leading sectors in the world economy, which is developing rapidly and is of interest and income to many people. In recent years, tourism has become a major contributor to world exports and accounts for 11% of global GDP. [1] In particular, deepening the liberalization of the economy, modernization of the country, and sustainable development of all sectors, especially pilgrimage tourism, which is one of the leading sectors of the service sector, are the basis of the success achieved in Uzbekistan. As the President of the Republic of Uzbekistan Sh. Mirziyoyev noted: "Uzbekistan is a convenient country for both travel and pilgrimage. [2] Because in our motherland, our ancestors, who are known and famous all over the world, have settled forever. The rich spiritual and cultural heritage they left behind is of international interest. very large. To further develop the field, it is necessary to improve the necessary infrastructure first. In Samarkand, there is a mausoleum of the great scientist Abu Abdullah Muhammad ibn Ismail ibn Ibrahim al-Bukhari, who is famous for his services in the Islamic world. The burial place of Imamal-Bukhari It is the village of Khartang in Payariq district, where the mosque built by Bukharakhoni Abdullah Khan is preserved [3]. Here we can see that the spiritual and cultural heritage of our ancestors has reached us. important issues are being faced.For example, the security of non-renewable items related to pilgrimage.Any tourist t should be prepared for and prevent any risks that may arise due to carelessness when visiting. Examples of these non-renewable items are flammable, breakable, and similar non-renewable items.